La reforma constitucional del Senado - Varela Suanzes-Carpegna, Joaquín (Teoría y Realidad Constitucional, 2006)
The main aim of this paper is to examine the constitutional reform of the spanish Senado, which has been announced by Mr. Rodríguez Zapatero in april 2004. But firstly I will have a look at the comparative Constitutional history with the purpose to analyse how other nations, over all USAand Germany, have organised their Parliament. I will examine also the controversy «unicameralism versus bicameralism» in the spanish constitutional history, including during the two years between the «Ley para la Reforma Política»and the Constitution of 1978. Then I will described briefly the composition andfunctions of the present Senado and I will resume the debate on this Chamberduring the last quarter of century, with special mention to the General Comission of the «Comunidades Autónomas» experience. Last, but not least, I will propose some constitutional reforms to transform the Senado into a true «territorialrepresentative Chamber», as it is defined in the article 69, 1 of the spanishConstitution.